2022
DOI: 10.1007/s11010-022-04536-8
|View full text |Cite
|
Sign up to set email alerts
|

Circadian disruption alters gut barrier integrity via a ß-catenin-MMP-related pathway

Abstract: We evaluated the mechanistic link between circadian rhythms and gut barrier permeability. Mice were subjected to either constant 24-h light (LL) or 12-h light/dark cycles (LD). Mice housed in LL experienced a significant increase in gut barrier permeability that was associated with dysregulated ß-catenin expression and altered expression of tight junction (TJ) proteins. Silencing of ß-catenin resulted in disruption of barrier function in SW480 cells, with ß-catenin appearing to be an upstream regulator of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 71 publications
4
6
0
Order By: Relevance
“…β-catenin, which shows regulatory effects on barrier integrity, was found to regulate both occludin and ZO-1 expression [ 78 ]. In support of these reports, circadian regulation of tight junction protein expression was also observed in intestinal cells [ 79 ].…”
Section: Circadian Rhythms In the Bbbsupporting
confidence: 53%
“…β-catenin, which shows regulatory effects on barrier integrity, was found to regulate both occludin and ZO-1 expression [ 78 ]. In support of these reports, circadian regulation of tight junction protein expression was also observed in intestinal cells [ 79 ].…”
Section: Circadian Rhythms In the Bbbsupporting
confidence: 53%
“…The molecular basis of the biological clock consists of a series of clock genes, including Bmal1, the circadian motor output cycle kaput (Clock), cyclic genes (Per1, Per2, and Per3), and cryptochrome genes (Cry1 and Cry2) (48).Our study found that Bmal1 mRNA expression was the only one that was significantly decreased at all time points in the CRD mice model, given its centrality in the biological clock system, we chose it as the main object of our study. Furthermore, we observed decreased expression of Bmal1 in the colon of mice with DSS-induced colitis, which is consistent with previous studies (16,39,49), suggesting that Bmal1 may be a key factor in the process of CRD affecting UC pathogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…109 Furthermore, Summa et al 110 showed oscillation of mRNA expression of occludin peaks during the rest phase (ZT0-4) of mouse colon tissue. To assess the mechanistic link between circadian rhythms and intestinal barrier permeability, Eum et al 111 exposed mice to constant 24-h light (LL) or a 12-h light/dark cycle (LD). Mice exposed to constant light had significantly increased intestinal barrier permeability, with decreased expression of β-catenin and decreased TJ protein expression.…”
Section: Oscillations and Daily Rhythms Of Flux Through The Bbbmentioning
confidence: 99%